STRENGTHENING AUTHENTIC LEADERSHIP, ORGANIZATIONAL CULTURE, TEACHER PROFESSIONALISM, AND TRUST IN IMPROVING TEACHER COMMITMENT TO SCHOOLS USING PATH ANALYSIS AND SITOREM ON TEACHERS AT A JOINT COOPERATION SCHOOL (SPK) IN JAKARTA - Tri Maryanto; Sri Setyaningsih; Rita Retnowati (SUJANA: Education and Learning Review, 2025)
This study aims to formulate strategies, methods, and optimal solutions to improve teachers' commitment to schools. These strategies are explored by examining the influence of authentic leadership, organizational culture, teacher professionalism, and trust on teacher commitment. This study is motivated by the limited research examining the enhancement of teacher commitment within the context of Joint Cooperation Schools (SPK) using a simultaneous path analysis and SITOREM approach. The method employed is a quantitative approach with a survey technique targeting 175 local teachers from 12 SPK high schools in Jakarta, selected through multistage random sampling. Data were collected using questionnaires and analyzed using path analysis to examine the direct and indirect effects between variables. The analysis was followed with SITOREM to identify priority indicators that should be improved or maintained in efforts to enhance teacher commitment. The results of the study indicate that the four independent variables—authentic leadership, organizational culture, teacher professionalism, and trust—have a positive and significant effect on teacher commitment. Trust was also found to be a mediating variable that strengthens the indirect influence of the other three variables on teacher commitment. The SITOREM analysis recommended strengthening the key indicators of each variable, with a priority on improving aspects of trust and professionalism. These findings contribute theoretically to the development of educational management science and provide practical recommendations for SPK schools in designing teacher development programs, strengthening work culture, and fostering authentic leadership.